Ultrasonic Sensitivity-Improved Fabry–Perot Interferometer Using Acoustic Focusing and Its Application for Noncontact Imaging - Qiangzhou Rong; Ruixiang Zhou; Yongxin Hao; Xunli Yin; Zhihua Shao; Tingting Gang; Xueguang Qiao (IEEE Photonics Journal)
An easily multiplexed fiber-optic Fabry–Perot interferometer (FPI)-based ultrasonic wave (UW) sensor has been proposed and used to experimentally demonstrate ultrasound wave imaging of seismic-physical models. The sensor probe comprises an interferometer formed by a free-standing gold foil and a cleaved optic-fiber tip. An acoustic focusing lens enhances the sensor's ultrasound sensitivity and assists with capability to multiplex multiple probes. Theoretical modeling of the focusing effect of the acoustic lenses and the ultrasonic responses of the probes are presented and analyzed. We present an experimental demonstration of time-division multiplexing of three fiber-optic Fabry–Perot sensors operating in air to reconstruct the shapes of physical models. The compact sensor has a symmetrical structure so that it presents a good directionality of ultrasound detection, making it valuable as an effective sensor for ultrasound scanning of physical models in air.